2022
DOI: 10.1108/ijwhm-03-2021-0070
|View full text |Cite
|
Sign up to set email alerts
|

Work alienation as a mediator between work from home-related isolation, loss of task identity and job insecurity amid the COVID-19 pandemic

Abstract: PurposeThis sudden disruption of work in the world due to the coronavirus disease 2019 (COVID-19) pandemic has led to unravelling situations hitherto unknown to researchers and therefore requires careful and thorough investigation. The aim of the study was to investigate the relationship between work from home (WFH) isolation, WFH loss of task identity and job insecurity amid COVID-19 pandemic WFH arrangements by focusing on information technology/information technology-enabled services (IT/ITES) sector employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…Job insecurity during COVID-19 had a significant and positive influence on professional isolation (β = 0.145; T-value = 3.456; p < 0.010); therefore, H8 can be accepted. The literature [25,71,72] pointed out that job insecurity is linked to employee isolation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Job insecurity during COVID-19 had a significant and positive influence on professional isolation (β = 0.145; T-value = 3.456; p < 0.010); therefore, H8 can be accepted. The literature [25,71,72] pointed out that job insecurity is linked to employee isolation.…”
Section: Resultsmentioning
confidence: 99%
“…In such contexts, job insecurity increases and employees develop legitimate fears regarding their organisational belonging, etc. [25,71,72]. Therefore, we assess that:…”
Section: Antecedents and The Effects Of Telework In A Pandemic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Anh et al (2022) argue that employees reported the lack of a healthy office desk and space to allow healthy working conditions, but the author's findings have reflected that some employers are providing office furniture or allowing employees to take their office facilities home with them. In addition, according to Mehta (2022), the theory of self-determination is useful was useful in knowing how employees managed to adjust and adapt to the rapidly to the conditions for working from home.…”
Section: Resultsmentioning
confidence: 99%
“…When the studies are examined in detail, it is seen that this process is often associated with two different concepts separately. These concepts are the concept of "alienation", which is one of the research areas of social psychology, and "social anhedonia", which is a neuropsychological concept [11][12][13][14].…”
Section: Original Articlementioning
confidence: 99%